The Contract or Agreement Business Law in Indonesia - Anirut Chuasanga (Sultan Agung Notary Law Review, 2023)
Agreement regulated in article 1313 of the Civil Code (KUH Perdata), namely "an act in which one or more people bind themselves to one or more other people". In contrast to an engagement which is a legal relationship, an agreement is a legal act. It is this legal act that gives rise to a legal relationship of engagement, so that it can be said that the agreement is the source of the engagement. Besides the agreement, we also know the term contract. Grammatically, the term contract comes from English, contract. Both agreements and contracts contain the same meaning, namely a legal act to bind the parties to each other in a legal relationship. The term contract is used more often in business practice.